ATTITUDES AND KNOWLEDGE OF PARENTS OF SCHOOL CHILDREN ABOUT HPV INFECTION AND VACCINATION IN THE COUNTRIES OF THE FORMER YUGOSLAVIA: REVIEW - Pavić, Katarina; Savić, Nikola; Perović, Dušica; Malenković, Goran (HEALTH CARE, 2025)
In 2022, cervical cancer was the fourth most common cancer among women worldwide, with over 660,000 new cases annually. It is caused by persistent infection with the human papillomavirus (HPV). The key measures for cervical cancer prevention are screening (Pap test) and the HPV vaccine. As of 2023, six types of HPV vaccines are available worldwide. According to the World Health Organization (WHO) strategy, if vaccination coverage of girls up to the age of 15 were to reach 90%, the disease could be eliminated. However, WHO member states have not yet exceeded a coverage rate of 55%, while the countries of the former Yugoslavia show significantly lower rates. The aim of this review paper is to analyze parents’ attitudes and knowledge regarding HPV vaccination of their children in the countries of the former Yugoslavia. Electronic databases (PubMed, Scopus, and Google Scholar) were searched using the following keywords in English: parental attitudes, vaccine acceptance, vaccine hesitancy, and HPV vaccine. Four articles meeting the inclusion criteria were identified. The analyzed studies showed that pediatricians’ recommendations have the greatest influence on parents’ acceptance of HPV vaccination. Studies conducted in Serbia found that girls are vaccinated more often than boys. Parents stated that HPV vaccination is insufficiently promoted, and that more attention should be dedicated to this issue in the future. It has been observed that parents are the target population for implementing educational interventions on HPV infection and vaccination in order to achieve higher coverage with this vaccine.
Keywords: HPV infection, HPV vaccine, parental attitudes, cervical cancer